2015
DOI: 10.1080/19443994.2015.1036778
|View full text |Cite
|
Sign up to set email alerts
|

Removal of COD, TSS and colour from palm oil mill effluent (POME) using montmorillonite

Abstract: A B S T R A C TThe adsorption of POME using natural clay, montmorillonite, has been investigated. The reductions of three important parameters (chemical oxygen demand, total suspended solids and colour) in various influencing factors have been determined. The optimum conditions for mixing speed of the stirrer, contact time, dosage of adsorbent, concentration of palm oil mill effluent (POME) and pH were 300 rpm, 90 min, 5 g/L, 25% POME and pH 7, respectively. The removal reached more than 95% for all parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…. The best fit for MOSF, based on the linearity ( R 2 ), was for the intra‐particle diffusion model, indicating that intra‐particle diffusion controls the whole process of adsorption . With chitosan, higher linearity was attained for the pseudo‐second order equation; it was then determined that the rate‐controlling step was chemisorption .…”
Section: Resultsmentioning
confidence: 99%
“…. The best fit for MOSF, based on the linearity ( R 2 ), was for the intra‐particle diffusion model, indicating that intra‐particle diffusion controls the whole process of adsorption . With chitosan, higher linearity was attained for the pseudo‐second order equation; it was then determined that the rate‐controlling step was chemisorption .…”
Section: Resultsmentioning
confidence: 99%
“…Membrane fouling could cause gross deterioration of the system performance in terms of filtration and operational energy utilization, as highlighted earlier. Therefore, the need to control the fouling is indispensable and this justified the previous studies reported on this critical area [67,110,161,[255][256][257][258]. The efforts devoted by the researchers have yielded some improvements such as membrane fouling control strategies and filtration.…”
Section: Mbr Major Drawbacksmentioning
confidence: 91%
“…With this, the permissible BOD discharge limit of POME has recently been reduced further from 100 mg/L to 20 mg/L [12]. Numerous alternative treatment techniques for POME have been studied by researchers, including aerobic submerged membrane bioreactor [13], anaerobic/aerobic bioreactor [14], activated carbon adsorption and ultrasound cavitation [15,16], membrane process [17,18], advanced oxidation process [19], photocatalytic degradation [9] and electrocoagulation [7]. However, most of these methods are either costly or triggering hostile effects to the environment.…”
Section: Introductionmentioning
confidence: 99%